Performance and Endurance Test of Preheater for Indirect Injection Diesel Engine Using Pure Plant Oil - Yuqa Satrio, Naufan
Pure vegetable oil is one of the alternative fuel used for power generation. With the high availability of plant that produced pure plant oils such as coconut and palm, it is expected to be a solution to energy independence on remote islands in Indonesia. However, the use of PCO and PPaO still hampered with the high viscosity so that the atomization in the fuel injection is bad. Regarding to that, it is necessary to build a preheater as a diesel engine modification. Preheater design utilizes heat from the exhaust gas to heat pure plant oil before entering the injector. Preheteater uses the principle of helical coil heat exchanger. Testing is done by measuring the rate of fuel consumption and temperatures entering and exit of both the oil and exhaust gas from preheater. Parameters that would be observed from the preheater performance test is heat exchanger effectiveness (?) and heat transfer on inner pipe surface temperature (Ts). Performace parameters will be compared after the endurance test for 32 hours. Based on the test, preheater used to heat the PCO have effectiveness of 63.54%. While the preheater used to heat PPaO have effectiveness of 65.98%. Preheater effectiveness declined on average by 3.38% and inner pipe surface temperature declined by 6.18oC for PCO usage. Meanwhile preheater used to preheat PPaO has its effectiveness declined on average by 7.85% and pipe surface temperature declined by 5.81oC after the endurance test for 32 hours.